I discepoli di Gesù nell’ora della prova (Gv 18–19) come luogo di rivelazione del Maestro - Grochowski, Zbigniew (The Biblical Annals, 2015)
The Passion Narrative in the Fourth Gospel is usually analyzed from the purely christological point of view. The number of monographs and articles that would pay attention to the ecclesiastical and anthropological aspect of the Passion of Jesus revealed in the conduct of his disciples in John 18–19 is quite limited. It seems that the “Hour of Jesus” is also the “hour of the trial of his followers” (cf. John 16:2, 4, 21, 32). The present study discusses this issue in John 18:1-14, 15-27; 19:24h-27, (35), 38-42 and presents different characterizations of Jesus’ disciples who appear as the locus of the revelation of their Master.